9 Left atrial force as a precise haemodynamic monitor in patients with hereditary haemochromatosis pre and post venesection. (7th October 2015) - King, G; Byrne, D; Bennett, K; Norris, S; Daly, C; Murphy, RT
Abstract : Background: Left atrial force (LAF) has been proven useful in assessing changes in diastolic performance in inherited cardiomyopathy. However, it is unclear whether LAF has the same potential in assessing diastolic performance in infiltrative disorders. Therefore the aim of the study is to examine whether changes in diastolic performance following treatment for Hereditary Haemochromatosis (HH) over a one year period can be assessed using LAF. Methods: We followed 49 patients with HH with elevated serum ferritin levels (852 mcg/L ± 189) at initial diagnosis and after undergoing treatment with venesection for 1 year. Diastolic myocardial function was measured by the ratio of mitral peak velocity of early filling (E) to early diastolic mitral annular velocity (e') (E/e' ratio). Left atrial volume (LAV) was measured by the biplane area/length method. Left atrial force was assessed according to the Newtonian principle, in which force (dynes) = mass—acceleration. Mass is defined by the product of the density of blood (i.e.1.06 g/cm 3 ) and the volume of blood passing through the mitral annulus during atrial contraction. Left atrial force was calculated by the Manning method expressed as, 0.53—mitral annular orifice area—(peak A velocity). Results: Follow up data are available of 25 of 49 subjects. There was no difference in age, gender, body surface area (P = 0.089) compared to 20 matched controls. Over the time course of treatment there was no significant change in the E/e as a marker of diastolic myocardial function (median change pre-post = 0, inter-quartile range (IQR: -0.8, 0.4), p = 0.55). There was a significant difference pre and post venesection in LAV (median pretreatment 24 ml/m 2, post 18 ml/m 2, p = 0.017) and serum ferritin (pre 851, mcg/L, post 239 mcg/L ± 101). We applied a non-parametric signed rank test and the median left atrial force was 5.6 kdynes pre- treatment and 4.4 kdynes post. LAF showed a significant decrease (median decrease = 0.6, (IQR 0, 1.60), p = 0.0004). Conclusion: LAF is a precise haemodynamic monitor for early detection of LA dysfunction and may help monitor response to treatment in patients with hereditary hemochromatosis.